Strengthening Religious Moderation Based on Majelis Taklim Through a Participatory Action Research (PAR) Approach in a Semi-Urban Environment - Syahril Siddik; Ahmad Yuzki Arifian Nawafi'; Didin Wahyudin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
Strengthening religious moderation in semi-urban communities is increasingly important in maintaining social harmony amid plurality. This community service research aims to describe the process and results of mentoring religious moderation values based on the Ar-Royan Tunggulsari Tulungagung Mosque Council. The approach used is Participatory Action Research (PAR) with the KUPAR (Know–Understand–Plan–Action–Reflection) cycle involving active congregations, mosque administrators, and the local community. Data were collected through participatory observation, group discussions, reflective interviews, and activity documentation. The findings show that the guidance succeeded in reconstructing the congregation's understanding of religious moderation from a normative to a conceptual concept, increasing sensitivity to diversity, and changing social interaction patterns to be more dialogical and inclusive. This transformation also had an impact on strengthening internal solidarity and social cohesion that was more adaptive to the dynamics of heterogeneity in the residential environment. These findings indicate that majelis taklim has the potential to become a space for practicing religious moderation through a deliberative participatory approach. The practical implication of this community service is a model for strengthening moderation that can be replicated in similar communities to encourage harmony and cross-group cooperation.